Solve for y -y+3=6

Math
-y+3=6
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
-y=6-3
Subtract 3 from 6.
-y=3
-y=3
Multiply each term in -y=3 by -1
Tap for more steps…
Multiply each term in -y=3 by -1.
(-y)⋅-1=3⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=3⋅-1
Multiply y by 1.
y=3⋅-1
y=3⋅-1
Multiply 3 by -1.
y=-3
y=-3
Solve for y -y+3=6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top